Introduction: transnational food (in)security. (2nd October 2018) - Webster, Emily; Zumbansen, Peer
ABSTRACT: Serving as introduction to the first Annual Transnational Legal Theory Symposium—with a focus on Transnational Food (In)Security—this essay provides an overview of the themes that stood at the centre of the conference and which pervade the symposium contributions. The topic of food concerns one of humanity's basic and profound aspects of survival. Universal and equal access to food is, at the same time, ridden with problems of power, inequality, distribution and implicated in old and new geopolitical conflicts. As such, 'food' has ties and is central to conditions of poverty and hunger, development and 'modernisation', transitional justice and rule of law reform around the world. As a problem of critique and scholarly inquiry, food prompts an inter-disciplinary assessment of the nature and different aspects of what is at issue here. The contributors to this symposium take us deep into the complexity of food and illustrate the challenges of adequately understanding and approaching questions of food security and food sovereignty in a globally interconnected world.